CAMPURAN PAKAN HERBAL UNTUK TERNAK AYAM KAMPUNG (Mixture Herbal Woof For Livestock Chicken Local) - Nurhapsa Nurhapsa; Yusriadi Yusriadi; Nurhaedah Nurhaedah (Equilibrium : Jurnal Ilmiah Ekonomi, Manajemen dan Akuntansi, 2017)
Abstrak: People rural same have local, it is one of species livestock not RAS (BURAS). Purpose have is to increase knowladge people so that residue farm to become food livestock. Raise in ceneral do traditional that is left prowl without food and stable. Raise to can do that semi intensive or intensive. Semi intencive is left during in the day and stabled in the night, while so that intencive is stabled all day and food although drink can control. For overcome problem society in raise the so do activity mixed woof herbal to livestok . This Acitivity do in kelurahan Ujung, kecamatan Lilirilau, kabupaten Soppeng South Sulawes. The target this activity are increase scale ownership, can exploited a material local as woof livestock and surface this activity are increase knowladge and income sociaty. Keyword: woof herbal, chicken local.